Molecular characterization of root-knot nematodes (Meloidogyne spp.) parasitizing potatoes (Solanum tuberosum) in South Africa - Moleleki, Lucy N. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.